2, 000 Year old β‐thalassemia case in Sardinia suggests malaria was endemic by the Roman period. Issue 2 (6th July 2017) - Viganó, Claudia; Haas, Cordula; Rühli, Frank J.; Bouwman, Abigail
Abstract: Objectives: The island of Sardinia has one of the highest incidence rates of β‐thalassemia in Europe due to its long history of endemic malaria, which, according to historical records, was introduced around 2, 600 years ago by the Punics and only became endemic around the Middle Ages. In particular, the cod39 mutation is responsible for more than 95% of all β‐thalassemia cases observed on the island. Debates surround the origin of the mutation. Some argue that its presence in the Western Mediterranean reflects the migration of people away from Sardinia, others that it reflects the colonization of the island by the Punics who might have carried the disease allele. The aim of this study was to investigate β‐globin mutations, including cod39, using ancient DNA (aDNA) analysis, to better understand the history and origin of β‐thalassemia and malaria in Sardinia. Materials and Methods: PCR analysis followed by sequencing were used to investigate the presence of β‐thalassemia mutations in 19 individuals from three different Roman and Punic necropolises in Sardinia. Results: The cod39 mutation was identified in one male individual buried in a necropolis from the Punic/Roman period. Further analyses have shown that his mitochondrial DNA (mtDNA) and Y‐chromosome haplogroups were U5a and I2a1a1, respectively, indicating the individual was probably of Sardinian origin. Conclusions: This is the earliest documented case of β‐thalassemia in Sardinia to date. The presence of such a pathogenic mutation and its persistence until present day indicates that malaria was likely endemic on the island by the Roman period, earlier than the historical sources suggest.